WTO AND REGIONALISM: A DEBATE - Shrawan Kumar Singh (Abhigyan, 2011)
With the future of the Doha Round uncertain, there has been a sharp increase in the number of bilateral and regional trade agreements. This has revived long-running arguments in international economics between those promoting global trade agreements and those favouring regional approaches. The difference between trade agreements and more general mechanisms for integration is often misunderstood. This debate often implies a false choice between regional versus global integration. The paper is not intended to be an exhaustive examination of the issues involved. The object is mainly to draw and sharpen the focus of attention on the problems of managing trade blocs within the WTO framework.